THE URGENCY OF UNDERSTANDING THE NEW PARADIGM OF PERFORMANCE MANAGEMENT - Nugroho, Sukmo Hadi (JOURNAL ASRO, 2024)
This paper discusses the significance of understanding the new paradigm of performance management, particularly in large-scale organizations and national contexts. The study identifies that poor organizational performance is often driven by suboptimal human resource management, ineffective performance systems, and unsupportive work environments. Drawing on case studies from both the public and private sectors, the paper emphasizes the critical role of human resources in achieving organizational success, particularly in the era of rapid technological change brought by Industry 4.0. The paper also highlights the Indonesian government's efforts to improve human resource quality and the nation's Human Development Index (HDI) through educational reforms and policy initiatives. By embracing a holistic approach to performance management and fostering collaboration between institutions, the paper argues that sustainable organizational growth and national development are achievable. The discussion includes strategies for effective performance management that integrate system-based thinking, human resource development, and modern technologies. Keywords: Human Resource Development, Integrate System Based Thingking, Performance Management.